2015
DOI: 10.3928/01477447-20150215-55
|View full text |Cite
|
Sign up to set email alerts
|

Periprosthetic Bone Remodeling Around Short Stem

Abstract: Total hip arthroplasty (THA) has become standard treatment for advanced degenerative changes of the hip. A few studies have reported promising clinical outcomes with the Metha stem fixated by metaphyseal anchoring. This study evaluated early bone remodeling around the Metha stem during 12 months of follow-up. The study population included 36 patients (18 women and 18 men) with a mean age of 50.4 years who underwent THA between 2009 and 2011 for advanced degenerative changes of the hip with the Metha stem. Pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 22 publications
2
18
0
Order By: Relevance
“…The Harris Hip Score (HHS) revealed good to excellent clinical results. These are comparable to other studies using the Metha 1 stem, 3,7,8 or other short stems. 1,5,6 Pain values decreased to 0.4 of 10 points.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The Harris Hip Score (HHS) revealed good to excellent clinical results. These are comparable to other studies using the Metha 1 stem, 3,7,8 or other short stems. 1,5,6 Pain values decreased to 0.4 of 10 points.…”
Section: Discussionsupporting
confidence: 89%
“…Over the years, dualenergy X-ray absorptiometry (DXA) became a proven method to examine changes of bone mineral density (BMD) around implants. [1][2][3][4][5][6][7][8][9] To describe changes of the interface between bone and femoral implants the Gruen zone system has been established as standard. Originally, it was developed for classifying zones of lucency on plain x-rays following the implantation of standard stems.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, short hip stems and even neck stems have become the latest concepts. These stems help preserve the femoral neck, keep the anatomical elasticity of the femur and introduce the forces in the upper part of the femur [18,51,[58][59][60][61][62][63][64]. And studies evaluated periprosthetic bone remodeling with DEXA showed a more balanced remodeling and favorable load transfer of the short stem in comparison to standard hip stem [16,51,[60][61][62][63][64][65].…”
Section: Implant-related Factorsmentioning
confidence: 99%
“…Some authors investigated the bone remodelling characteristics of the femur after THA with a METHA stem by using DEXA assessment and adapting Gruen zones (R1 to R7) to the short stem design. 89 92 In all studies including 176 hips with at least one year of follow-up, the bone mineral density (BMD) significantly increased in the lateral regions (R2 and R3) and significantly decreased in the proximal regions (R1 and R7). On the other hand, changes in distal (R4), distal-medial (zone 5) and lesser trochanter (R6) regions were less relevant and reliable across the analysed studies.…”
Section: Stem Features and Outcomesmentioning
confidence: 99%